MERDEKA BELAJAR DALAM PEMBELAJARAN KALKULUS BERBASIS PENGAJUAN DAN PEMECAHAN MASALAH - Novi Andri Nurcahyono; Sumiati Sani (Prodi Pendidikan Matematika, FKIP, Universitas Balikpapan, 2020)
The independent learning program focuses on how learning is free to innovate and improve literacy and numeracy skills. Both of these capabilities are still low in Indonesia. Literacy and numeracy skills are increasingly important in a digital environment, but it is challenging to develop approaches to learning a subject, for example, in calculus learning which is often considered rigid and traditional learning. This needs to be renewed using the concept of freedom of learning based on problem-posing and problem-solving. Calculus learning by involving both of these approaches will create democratic learning because the characteristic of this learning gives sovereignty to students to be independent in learning. Thus, students are free to think critically and creatively in finding information sources digitally and non-digitally as well as expressing their ideas on mathematical problems that exist in real life. Digital literacy and numeracy abilities of students will be formed, and the result of students will have four soft skills, namely, creativity, critical thinking, communication, and collaboration.